Preparation of Core-Shell Catalyst by in situ Growth Method in Water-in-Oil Microemulsion - Chen, Y.; Cao, T.; Wang, Y.; Xuan, H.; Zhou, Z.H.; Feng, S.J. (Asian Journal of Chemistry, 2014)
A type of core-shell catalyst CuO-ZnO-Al2O3/ZSM-5 was prepared for direct synthesis of dimethyl ether from syngas. A water-in-oil microemulsion made up of liquid paraffin, Span 80 and water phase was used to prepare both the core and core-shell catalyst. The water phase was consisted of core growth medium for core preparation or core sol for core-shell preparation. The dispersion medium of core sol was the growth medium and shell would layer on the core directly. Transmission electron microscopic images showed the core particles were in nano-size and coated by shell successfully. EDS was used to test quality percents of Cu, Zn and Al. The crystal structure of core and shell was described by XRD. This original preparation method of in situ growth in microemulsion can give a novel inspiration to the core-shell constitute material which can realize the combination of two and more sequential reactions with many synergistic effects.